Study of the space–time transition and spatial spillover effects of tourism green production efficiency in the Yangtze River Delta—a reanalysis from the perspective of tourism carbon sinks - Shi, Pengfei; Long, Huibing; Yao, Yikun; Li, Xingming; Wang, Xinrui (Frontiers in Environmental Science, 2023)
In this paper, the tourism carbon sink is included in the measurement framework, and the TGPE of 41 cities in the Yangtze River Delta region from 2011 to 2019 is estimated by the Super-SBM model. Furthermore, kernel density estimate, spatial autocorrelation, Markov chain and spatial Durbin model are further integrated to explore its spatiotemporal evolution process, spatial effects and influencing factors.The results show that (1) TGPE in the Yangtze River Delta has been increasing during the study period. The high-efficiency and low-efficiency areas of the TGPE have a bipolar pattern characterized by "low-low convergence" and "high-high convergence". (2) There is considerable spatial variation in TGPE from north to south. The number of hot spots and sub-hot spots increases in volatility, whereas the number of sub-cold spots and cold spots decreases. (3) Although cities with low levels of TGPE have a higher probability of moving to the next level, grade transformation across hierarchies is difficult to attain. When considering the factor of adjacent types and the influence of spatial lag on the transfer probability. (4) The positive spatial spillover effects of TGPE is significant. At the same time, economic development level , transport accessibility and tourism industry agglomeration have positive spillover effects on neighboring cities. Conversely,urbanization level and openness level have negative spillover effects.